Glencoe mathematics : - Collins, William (Glencoe/McGraw-Hill, 1998)
This book includes 14 chapters: Chapter 1: Tools for problem solving; Chapter 2: Applications with decimals; Chapter 3: Statistics and data analysis; Chapter 4: Patterns and number sence; Chapter 5: Applications with fractions; Chapter 6: An introduction to algebra; Chapter 7: Integers; Chapter 8: Investigations in geometry; Chapter 9: Area; Chapter 10: Surface area and volume; Chapter 11: Ratio, proportion, and percent; Chapter 12: Applications with percent; Chapter 13: Discrete math and probability; Chapter 14: Functions and graphs.